Intravenous transplantation of olfactory bulb ensheathing cells for a spinal cord hemisection injury rat model. Issue 12 (December 2019) - Zhang, Lijian; Zhuang, Xiaoqing; Chen, Yao; Xia, Hechun
Cellular transplantation strategies utilizing intraspinal or intrathecal olfactory ensheathing cells (OECs) have been reported as beneficial for spinal cord injury (SCI). However, there are many disadvantages of these methods, including additional trauma to the spinal cord parenchyma and technical challenges. Therefore, we investigated the feasibility and potential benefits of intravenous transplantation of OECs in a rat hemisection SCI model. OECs derived from olfactory bulb tissue were labeled with quantum dots (QDs), and their biodistribution after intravenous transplantation was tracked using a fluorescence imaging system. Accumulation of the transplanted OECs was observed in the injured spinal cord within 10 min, peaked at seven days after cell transplantation, and decreased gradually thereafter. This time window corresponded to the blood–spinal cord barrier (BSCB) opening time, which was quantitated with the Evans blue leakage assay. Using immunohistochemistry, we examined neuronal growth (GAP-43), remyelination (MBP), and microglia (Iba-1) reactions at the lesion site. Motor function recovery was also measured using a classic open field test (Basso, Beattie and Bresnahan score). Compared with the group injected only with QDs, the rats that received OEC transplantation exhibited a prominent reduction in inflammatory responses, increased neurogenesis and remyelination, and significant improvement in motor function. We suggest that intravenous injection could also be an effective method for delivering OECs and improving functional outcomes after SCI. Moreover, the time course of BSCB disruption provides a clinically relevant therapeutic window for cell-based intervention.